PENGARUH PENGETAHUAN DAN FAKTOR KELUARGA TERHADAP KEBERLANGSUNGAN USAHA INDUSTRI GARAM DI KECAMATAN JANGKA - mauliza, mauliza; Wahyuni, Sri; Nova, Nova (Fakultas Ekonomi Universitas Almuslim Bireuen, 2023)
This research aims to explain the influence of knowledge and family factors on the sustainability of the salt industry business in Panjang District. The type of data is primary data using quantitative research methods and multiple linear regression model analysis. The results of this research state that knowledge influences the sustainability of the salt industry business. Family factors influence the sustainability of the salt industry business. Simultaneously, knowledge and family factors influence the sustainability of the salt industry business in Panjang District by 20.6%.